Characterization of the in Vitro Metabolic Profile of Evodiamine in Human Liver Microsomes and Hepatocytes by UHPLC-Q Exactive Mass Spectrometer - Zhang, Zhaowei; Fang, Tianzi; Zhou, Hongyun; Yuan, Jie; Liu, Qingwang (Frontiers in Pharmacology, 2018)
Evodiamine is an indoloquinazoline alkaloid isolated from the fruit of Evodia rutaecarpa, which has a wide range of pharmacological effects like anti-tumor and anti-inflammatory effects. This study was intended to investigate the metabolic characteristics of evodiamine in human liver microsomes and hepatocytes by ultra-high performance liquid chromatography (UHPLC) coupled with a Q Exactive Mass mass Spectrometerspectrometer. A total of twelve phase I metabolites were detected in human liver microsomes; whereas in human hepatocytes a total of nineteen metabolites, including seven phase II metabolites were detected. The structures of the metabolites were characterized based on their accurate masses, fragment ions, and chromatographic retention times. Four metabolites (M1, M2, M5 and M7) were further unambiguously confirmed by matching their retention times, accurate masses and fragment ions with those of their reference standards. Among these metabolites, twelve metabolites are first identified (M2, M5-M8, M10-M13 and M17-M19). The current study revealed that oxygenation, N-demethylation, dehydrogenation, glucuronidation and GSH conjugation were the major phase I metabolic reaction, and glucuronidation and GSH conjugation were the major phase II metabolic pathways for evodiamine. This study elucidated the detailed metabolite profiles of evodiamine, which is helpful in predicting in vivo metabolism of evodiamine in human body and in understanding the elimination mechanism of evodiamine and, in turn, the effectiveness and toxicity.